2021
DOI: 10.1590/1807-1929/agriambi.v25n2p132-138
|View full text |Cite
|
Sign up to set email alerts
|

Phytomass and production components of colored cotton under salt stress in different phenological stages

Abstract: Scarcity of good quality water is a limiting factor for irrigated agriculture, especially in semi-arid regions, which induces the use of waters with high salt concentration in crop irrigation. In view of the above, the objective of this study was to evaluate the phytomass accumulation and production components of colored cotton genotypes during the different development stages, under conditions of high salinity, with plants grown in lysimeters under greenhouse conditions, at the Center for Technology and Natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The volume applied to each pot, per irrigation event, was estimated individually using the water balance, according to Equation (1). A 20% leaching fraction was used monthly to remove excess salts from the ground [42]. Irrigation was carried out daily, at 5:00 p.m., by applying the water volume corresponding to the demand of the plant undergoing each treatment.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…The volume applied to each pot, per irrigation event, was estimated individually using the water balance, according to Equation (1). A 20% leaching fraction was used monthly to remove excess salts from the ground [42]. Irrigation was carried out daily, at 5:00 p.m., by applying the water volume corresponding to the demand of the plant undergoing each treatment.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…Irrigation with salt water in the vegetative growth stage has a lesser negative impact on seed production than in the fruiting stage. 48 Using water with different electrical conductivities and adding nitrogen, phosphorus and potassium salts can alleviate salt stress in plants by promoting ion homeostasis. 49,50 It has been reported that a mixture of organic matter, sulfur, and gypsum can reduce soil salinity and maintain soluble and exchangeable cations, promoting plant growth.…”
Section: Salinity Stressmentioning
confidence: 99%
“…In general, salt excess in the soil and/or water causes osmotic and ionic deleterious effects, especially in vegetables such as bell pepper (Lima et al, 2015;Soares et al, 2021). In irrigation-dependent crops, the use of highsalinity water can limit plant growth and production as it reduces the osmotic potential of the soil solution, causing ionic effects such as toxicity and nutritional imbalance (Lima et al, 2018;Barros et al, 2021).…”
Section: Introductionmentioning
confidence: 99%